5PSeq Explorer Data Freeze - Stevens, Irene; Pelechano, Vicent (Karolinska Institutet, 2026)
This data freeze accompanies 5PSeq Explorer and it contains 775 5PSeq datasets compiled from 18 published studies interrogating various aspects of biology at the interface of mRNA decay and translation, including both genetic and environmental perturbations. To enable comparability across conditions and cross-species we processed all data uniformly (see Methods). The generated database consists of: (1) metadata, (2) raw processed counts files of amino acid, codon, frame preferences, metagene counts around start and termination sites, additional count files as documented on the Fivepseq package output documentation, and (3) RNA composition.

For Eukaryotes, the collection consists of 378 yeast samples (Ascomycota phylum) with an overrepresentation for Saccharomyces cerevisiae (n= 340). For bacteria, we provide 397 samples across Actinomycetota, Bacillota, Bacteroides, Bacteroidota, Proteobacteria, Pseudomonadota and Verrucomicrobiota phyla with an overreprepresentation for Bacillus subtilis (n= 67) and Aggregatibacter actinomycetemcomitans (n=59).

Denna datafrysning medföljer 5PSeq Explorer och innehåller 775 5PSeq-dataset sammanställda från 18 publicerade studier som undersöker olika aspekter av biologi vid gränssnittet mellan mRNA-sönderfall och translation, inklusive både genetiska och miljömässiga störningar. För att möjliggöra jämförelse mellan olika förhållanden och mellan arter bearbetade vi all data enhetligt (se Metoder). Den genererade databasen består av: (1) metadata, (2) råa bearbetade räkningsfiler för aminosyra, kodon, rampreferenser, metagenräkningar kring start- och termineringsställen, ytterligare räkningsfiler som dokumenterats i Fivepseq-paketets utdatadokumentation och (3) RNA-sammansättning.

För eukaryoter består samlingen av 378 jästprover (Ascomycota phylum) med en överrepresentation för Saccharomyces cerevisiae (n = 340). För bakterier tillhandahåller vi 397 prover från Actinomycetota, Bacillota, Bacteroides, Bacteroidota, Proteobacteria, Pseudomonadota och Verrucomicrobiota phyla med en överrepresentation för Bacillus subtilis (n=67) och Aggregatibacter actinomycetemcomitans (n=59).
5PSeq Explorer-datafrysning
Keywords: Investigative Techniques; Utredningsmetoder; Gene Expression Profiling; Genuttrycksprofilering; RNA; RNA SEQUENCING; SCIENCE AND TECHNOLOGY; VETENSKAP OCH TEKNOLOGI; Biotechnology; Bioteknik; Medical and Health Sciences; Medicin och hälsovetenskap; Medical Genetics and Genomics; Medicinsk genetik och genomik; Cell and Molecular Biology; Cell- och molekylärbiologi